Meningkatkan Hasil Belajar Siswa Pada Pelajaran Matematika Di Kelas IX-7 Melalui Pendekatan Pembelajaran Saintifik Di SMP Negeri 2 Tanjung Morawa Pada Tahun Pelajaran 2019/2020 - Juita Juita (Pusdikra Publishing, 2022)
The aims of this study were to: Improve the learning outcomes of Class IX-7 students through a scientific learning approach at Tanjung Morawa 2 Public Middle School in the 2019/2020 Academic Year. The method used in this research is the Classroom Action Research Method using 2 cycles. The subjects of this study were 30 students of Class IX-7 at SMP Negeri 2 Tanjung Morawa. The instruments used to obtain data are tests, questionnaires and observations. The score range for the test is 1-100. The data analysis technique used is to use the calculation of the number of students' average scores, the percentage of students who have completed and the percentage of students who have not completed. The results of this study indicate (1) there is an increase in learning outcomes by applying a scientific learning approach with the following results, (2) there is an increase in the average student learning outcomes, where in the initial test the average student learning outcomes is 44.67, in the first cycle I increased to 66.67 then in cycle II it increased again to 74.33; there was an increase in the number of students who completed, where in the initial test the number of students who passed was only 0%, increasing to 66.67% in cycle I then increasing again to 83.33% in cycle II. (3) there was a decrease in the number of students who did not complete, where in the initial test the number of students who did not complete reached 100%, in cycle I it decreased to 33.33% then in cycle II it decreased again to 16.67% in other words only 5 students only those who get a score of 60 and the rest (25) students get a score above 70.